FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN: STUDI KASUS KABUPATEN/KOTA DI ACEH - Munawir Munawir; Rita Meutia (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2021)
Abstract This study aims to examine the effect of audit findings, central government transfers and level of regional wealth on the financial performance of district/city governments in Aceh Province. The object of research is the report on the results of the examination of the Regional Financial Management Report (LHP-LKPD) and the Budget Realization Report (LRA) of 23 district/city governments in Aceh Province. The research data was obtained through the website of the Information Management and Documentation Officer (PPID) of the Indonesian Financial Audit Agency (BPK-RI), as many as 115 LHP-LKPD and LRA, from 2014 to 2018. Data analysis using software eviews 9 in the form of panel data regression. Based on the research results, audit findings and central government transfers have a negative effect on financial performance. This means that the higher the audit findings and government transfers, the lower the financial performance of the regional government. It is different with the level of regional wealth which has a positive effect on the financial performance of local governments, this indicates that an increase in regional wealth will increase the financial performance of local governments.